Prevalence of feline immunodeficiency virus (FIV) and feline leukaemia virus (FeLV) in cats in the center of Risaralda, Colombia - Santisteban, Rafael Ricardo (2021)
The aim of this study was to establish the seroprevalence of infection of the feline leukemia virus (ViLeF) and the feline immunodeficiency virus (FIV) in serum samples from felines evaluated with suspected retroviral infection in veterinary centres of the municipalities of Pereira, Dosquebradas and Santa Rosa de Cabal, department of Risaralda, Colombia and sent to the EjeLab Laboratory. A retrospective study was carried out on the results of serology with a commercial kit for immunochromatography (Bionote®) between March 2017 and July 2018. The age, breed and sex of the animals were documented. In total, 388 samples were analysed, being 18.3% (71) positive for FIV and 25.8% (100) positive for ViLeF. Retroviral coinfection was observed in 8.2% (32) of the animals.